2017
DOI: 10.1021/acsenergylett.7b00620
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Organic Alloys in Ternary-Blend Solar Cells with Two Acceptors Having Energy-Level Offsets Exceeding 0.4 eV

Abstract: Recent studies demonstrated that with proper selection of chemically compatible constituents the open-circuit voltage (V oc ) of ternary-blend solar cells can be tuned across the composition window of the active layer. In this study, we probed the limit of the offset between the lowest unoccupied molecular orbital (LUMO) energy levels of the two acceptors in ternary blends containing one donor and two acceptors. We demonstrate, for the first time, that ternary-blend active layers with two acceptors having an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…It is possible to reduce E loss of PBDB-T:IEICO-4F:3TT-FIC-based ternary PSCs to obtain a large V OC value. [30,51] To evaluate the photovoltaic performance of our system and unravel the nature of its high V OC and small E loss value, photoluminescence (PL) quenching and time-resolved PL (TRPL) were employed to investigate the exciton dissociation and energy transfer at the donor/acceptor (D/A) interface. www.advopticalmat.de PBDB-T:IEICO-4F and IEICO-4F:3TT-FIC, and ternary films of PBDB-T:IEICO-4F:3TT-FIC).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible to reduce E loss of PBDB-T:IEICO-4F:3TT-FIC-based ternary PSCs to obtain a large V OC value. [30,51] To evaluate the photovoltaic performance of our system and unravel the nature of its high V OC and small E loss value, photoluminescence (PL) quenching and time-resolved PL (TRPL) were employed to investigate the exciton dissociation and energy transfer at the donor/acceptor (D/A) interface. www.advopticalmat.de PBDB-T:IEICO-4F and IEICO-4F:3TT-FIC, and ternary films of PBDB-T:IEICO-4F:3TT-FIC).…”
Section: Resultsmentioning
confidence: 99%
“…[25,26] Zhang's group reported a record PCE value of over 16% by using ternary films as the photoactive layer. [27] Notably, several excellent groups, such as Brabec's group, [28] Yang's group, [29] Thompson's group, [30] Cao's group, [31] Zhan's group, [32] and Hou's group, [33] have summarized the progress in ternary PSCs. According to the previous reports, three high photovoltaic parameters can hardly be simultaneously achieved in one binary PSC, which is limited by the intrinsic properties of the used materials.…”
Section: Introductionmentioning
confidence: 99%
“…The highest occupied molecular orbital (HOMO) level and the lowest unoccupied molecular orbital (LUMO) level of the third component are vital parameters to form efficient charge transport channels in ternary active layers with two donors or acceptors, respectively. Meanwhile, the appropriate energy levels of the third component can achieve relatively high open circuit voltage (V OC ) compared with the host binary PSCs, leading to the minimal energy loss by employing ternary strategy [15,[25][26][27][28][29][30][31]. Most of efficient ternary PSCs work under alloy-like model, which were well designed by employing two donors or two acceptors with good compatibility, appropriate energy levels and complementary absorption spectra [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Thompson and coworkers reported that the utilization of the PC 61 BM:P3HT75‐ co ‐EHT25:P3HTT‐DPP system is a practical strategy to improve the V oc and efficiency of ternary OSCs . A previous report suggested that the V oc of ternary OSCs was defined by the offset between the higher of the two HOMO energy levels of the donors and the LUMO energy level of the acceptor in two‐donors/one‐acceptor ternary blends . Alloy‐based ternary blends, comprising of a fullerene‐derivative acceptor and a nonfullerene acceptor, have been demonstrated for increasing the V oc of ternary OSCs.…”
Section: Introductionmentioning
confidence: 99%